Therapeutic role of d-pinitol on experimental colitis via activating Nrf2/ARE and PPAR-γ/NF-κB signaling pathways. Issue 6 (24th February 2021) - Lin, Yinsi; Wu, Yulin; Su, Jianhui; Wang, Mingqiang; Wu, Xiaoli; Su, Ziren; Yi, Xiaoqing; Wei, Long; Cai, Jian; Sun, Zhanghua
Abstract : d -Pinitol can be a food supplement exerting anti-colitis effects via Nrf2/ARE and PPAR-γ/NF-κB signaling pathways. Abstract : Ulcerative colitis is a recrudescent intestinal inflammation coupled with diarrhea, weight loss, pus, and blood stool, which seriously impacts the quality of patient life. d -Pinitol, which can be a food supplement isolated from the food plant-like soybeans, Ceratonia siliqua Linn and Bruguiera gymnorrhiza, has been proved to show anti-oxidative and anti-inflammatory effects. However, the potential mechanism of d -pinitol still remains ill-defined contemporarily. In the current study, the therapeutic effect and potential mechanisms of d -pinitol against colitis were investigated. Oxidative stress and inflammation of experimental colitis were caused by 3% DSS treatment once daily for 7 days. During DSS treatment, the mice of the positive drug group and three other groups were orally administered SASP or d -pinitol once daily. Clinical symptoms were analyzed, and macroscopic scores were calculated. The levels of oxidative and inflammatory cytokines were measured using assay kits and RT-PCR. Additionally, the protein expression of the Nrf2/ARE pathway and PPAR-γ was measured by Western blot. Results showed that d -pinitol enormously alleviated DSS-induced bodyweight loss, colon shortening, and histological injuries, achieving a therapeutic efficacy superior to SASP. Moreover, the oxidative stress and colonic inflammatory response were mitigated. d -pinitol not only significantly activated the Nrf2/ARE signaling pathway via facilitating the translocation of Nrf2 from sitoplazma to cytoblast, upregulating the protein expression levels of GCLC, GCLM, HO-1, and NQO1, but also improved the PPAR-γ level by binding to the active site of PPAR-γ, when suppressing NF-κB p65 and IκBα phosphorylation. In conclusion, d -pinitol exhibited a dramatic anti-colitis efficacy by activating the Nrf2/ARE pathway and PPAR-γ. Hence, d -pinitol may be a promising therapeutic drug against UC in the future.